Illuminating the intricate role of genetic factors in chronic low back pain: from the molecular basis of onset to the determination of susceptibility and the search for novel therapeutic avenues - Ding-Qiang Chen; Zhi-Qiang Que; Wen-Bin Xu; Ke-Yi Xiao; Nai-Kun Sun; Jin-Yi Feng; Gang Rui (European Journal of Medical Research)
Abstract Background Interleukin 6 receptor (IL6R) inhibitors are effective drugs as therapy for rheumatoid arthritis (RA). However, few studies on IL6R inhibition for relieving chronic low back pain (CLBP) have been conducted. These existing studies are plagued by issues such as small sample sizes and inconsistent inclusion criteria. With advances in genomics, more and more evidence is revealing the role of heritability in the etiology of disease, and Mendelian randomization (MR) analyses are being used more broadly to infer causation. MR analysis was used in the present study to investigate the effect of IL6R inhibitors on CLBP. Methods IL6R single nucleotide polymorphisms (SNPs) from Europe were selected from online databases. C-reactive protein (CRP) levels were utilized as an exposure factor, RA was employed as a positive control, and two CLBP-related genome-wide association studies (GAWS) data were used as primary outcomes for drug-targeted MR analyses for examining causality between IL6R inhibitors and CLBP. In addition, repeated analyses were also performed using different GWAS data related to exposure to test the stability of the results. Results IL6R inhibitors significantly reduced the risk of CLBP, ukb-a-346 (OR: 0.9564, 95% CI 0.9353–0.9774, P = 3.35 × 10–05), ukb-b-8463 (OR: 0.9558, 95% CI 0.9380–0.9737, P = 7.15 × 10–07). Moreover, repeated analyses using different GWAS data yielded similar results: ukb-a-346 (OR: 0.9494, 95% CI 0.9269–0.9719, P = 5.98 × 10–06), ukb-b-8463 (OR: 0.9502, 95% CI 0.9311–0.9693, P = 1.58 × 10–07). Conclusion The results of this MR study indicate that IL6R may contribute to the pathogenesis of CLBP and that inhibition of IL6R reduces the risk of CLBP. These findings may guide future studies and offer more favorable drug choices for individuals at risk of CLBP.